Introduction of a spectrophotometric method for salivary iodine determination on microplate based on Sandell-Kolthoff reaction - Oblak, Adrijana (Radiology and oncology (Ljubljana), 2024)
Background. Iodine is an essential element for the synthesis of thyroid hormones. Therefore, a reliable marker of iodine supply is important. Iodine is predominantly excreted via kidneys, but also via salivary glands. Our aim was to introduce a new and simple method for determination of salivary iodine concentration (SLIC). Materials and methods. Self-prepared chemicals and standards for Sandell-Kolthoff reaction on microplate with ammonium peroxydisulfate (AP) in the range 0-400 µg/L were used. Suitability of water-based standards (WBS) and artificial saliva-based standards (ASS) for standard curve were tested. We followed standards for method validation, defined concentration of used AP and compared our results with Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Results. WBS gave more reliable results than ASS as an underestimation of iodine concentration was found for ASS. LoB was 6.5 µg/L, LoD 12.0 µg/L, therefore analytical range was 12-400 µg/L. Intra- and inter-assay imprecisions at iodine concentrations, namely 20, 100, 165, and 350 µg/L were 18.4, 5.1, 5.7, and 2.8%, respectively, and 20.7, 6.7, 5.1, and 4.3%, respectively. Suitable molarity of AP was 1.0 mol/L and showed no difference to 1.5 mol/L (P values for samples with concentration 40, 100, and 150 µg/L, were 0.761, 0.085, and 0.275, respectively), whereas there was a significant change using 0.5 mol/L (P<0.001). Saliva samples could be diluted up to 1:8. There was no interference of thiocyanate and caffeine up to 193.5 mg/L. Our original method was comparable to ICP-MS. Spaerman coefficient was 0.989 (95% CI: 0.984-0.993). Conclusions. The new method for SLIC determination is in excellent agreement with ICP-MS and easy-to-use.
Keywords: jod; koncentracija joda v slini; masna spektrometrija induktivno sklopljene plazme; Sandell-Kolthoffova reakcija; ščitnični hormoni